Why The Better Angels of Our Nature Must Hate the State - Hanna, Robert (Con-Textos Kantianos. International Journal of Philosophy, 2017)
In this brief reply to Anne Margaret Baxley’s comments on my paper, “Exiting the State and Debunking the State of Nature,” I respond to her two critical worries about my thesis that there is an unbridgeable gap between Kant’s political theory, which is classically liberal, and his ethics/theory of enlightenment/moral theology, which is anarchist: (i) that Kant’s strong moral epistemic skepticism in the Groundwork about knowing the true motives of our choices and actions, requires coercive State intervention in order to ensure that we heed mutual relations of external freedom and do our juridical duties, and (ii) that the overall crookedness of the human timber, i.e., our almost inevitable empirical tendency to fall short of autocracy, requires the very same State interventions for the very same moral-political straightening purposes. I argue that (i*) Kant isn’t the moral epistemic skeptic he’s standardly taken to be—on the contrary, we have veridical, direct, occurrent, essentially non-conceptual, non-empirical awareness of autonomous choices and actions, via The Fact of Reason, and (ii*) that coercing people to be morally good necessarily undermines the moral worth of their choices and actions and turns them into nothing but well-oiled, law-abiding robots of the State—so we must exit the State in order to belong to an ethical community instead, i.e., Kantian anarchism; hence my unbridgeable-gap thesis still stands. I end by self-advertising for existential Kantian cosmopolitan anarchism.